POROUS IMPLANT MATERIALS AND RELATED METHODS (2018)
Provided are porous, biocompatible implant bodies and materials. These materials suitably comprise a population of randomly arranged and entangled thermoplastic constituents, with at least some of the constituents being bonded to one another The implant bodies are capable of being manipulated at room temperature from a first shape to a second shape, and of maintaining the second shape at about internal body temperature. Also provided are related methods of fabricating such implants and installing the implants into a subject.